MYTH AND SOCIAL IMAGINATION: TRADITIONAL VILLAGE PRESERVATION CONCEPT (CASE STUDY: KAMPUNG ADAT KUTA, CIAMIS, WEST JAVA) - Enny S. Sardiyarso; Popi Puspitasari (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2018)
AbstractGenerally, the reality of empirical experience is used as a reference in the settlement spatial arrangement. In this study, however, the form of myth and imagination affects spatial arrangement and environmental conservation. Spatial arrangement of settlements in Kampung Kuta, Ciamis, West Java is based on historical imaginative mythical thoughts of the past about the Idea of Keraton Wurung. The thought has positively impacted on the sustainability of environmental preservation in the present. The study was conducted based on qualitative-explorative approach by interviewing some key informants of local population. In terms of verification, the findings are being compared among the concept of spatial layout of current Kampung Adat Kuta and the general settlement theory as well as the concept of kampung in Priangan of the myth-imaginative-based spatial concept. The findings of the study suggest that conservation measures are based on the respect of the sacred imaginative of the palace and the ancepan that are considered as the important components of the palace and need to be maintained its sustainability. The control of human behavior in conservation efforts refers to: prohibitions and obligations to maintain harmony by considering the arrangements of ancient, balance, and management of natural resources that ensure the sustainability of life. Keywords: imaginary-myth, Kampung Adat Kuta, environmental preservation.